The Design of Closed Square RR Loaded 2-Port MIMO for Dual Band Applications - Bora, P.; Pokkunuri, P.; Madhav, B. T. P. (Engineering, Technology & Applied Science Research, 2022)
In this paper, a closed square ring resonator loaded 2-port Multi Input Multi Output (MIMO) is proposed for dual-band applications in the S and C band. The presented antenna model is designed by loading it in FR-4 substrate with a feedline of 50Ω and loaded with SRR for the enhancement of isolation and radiation pattern. Ansoft HFSS is used to obtain the simulated parameters of the model for the frequency ranges of 2.2-2.5 and 6-6.3GHz. Measurements confirm the characteristics of the fabricated antenna that were speculated with the simulation results with a little shift in frequencies. The diversity parameter performance analysis justifies the working performance of the 2-port MIMO for WiFi, WLAN, and ISM band applications.